Liturgical perspectives : prayer and poetry in light of the Dead Sea scrolls : proceedings of the Fifth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 19-23, January, 2000 - Chazon, Esther G.; Clements, Ruth.; Pinnick, Avital. (Studies on the Texts of the Desert of Judah, 2003)
The papers published in this volume were presented at the Fifth Orion International Symposium (Jerusalem, 2000), which focused on prayer and poetry in light of the Dead Sea Scrolls. The volume examines the recently published poetical and liturgical texts from Qumran against the background of Second Temple Judaism, its biblical antecedents, and later rabbinic developments. The essays treat a variety of prayers and religious practices, as well as major issues in the history of Jewish liturgy. Topics range from magic, mysticism and thanksgiving to lamentation, fast day rituals, communal worship, and the relationship between the prayers from Qumran and the traditional Jewish prayers. The application of new Scrolls material to this breadth of topics constitutes an important contribution to the study of religious poetry, religious practice, and liturgy.